PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. GARAM KALIANGET SUMENEP - Arifin, Fausi; Rahman, Hairul; Katsir Al Aziz, Moh Sofwan; Hidayat, Nurul (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
Employee productivity is a critical factor in determining a company’s success. Two key aspects that play a significant role in enhancing productivity are training and motivation. This study aims to analyze the influence of training and motivation on employee productivity at PT Garam Kalianget. The research employs a quantitative approach by collecting data through questionnaires distributed to employees. Data analysis is conducted using multiple linear regression to examine the relationship between training, motivation, and work productivity variables. The findings reveal that effective training has a positive and significant impact on work productivity. Similarly, high levels of motivation significantly enhance employee performance. The study concludes that companies must improve the quality of training and provide optimal motivational support to boost employee productivity.